A Comprehensive Characterization of the Differences in Meat Quality, Nonvolatile and Volatile Flavor Substances Between Taoyuan Black and Duroc Pigs - Hanjing Shi; Sisi Chen; Wenyue Zhou; Junfei Xu; Zekun Yang; Liu Guo; Qilong Li; Qiuping Guo; Yehui Duan; Jianzhong Li; Fengna Li (Foods)
To compare the differences in meat quality between obese-type Chinese pig breeds and lean-type foreign pig breeds, we selected Taoyuan Black (TB) pigs and Duroc pigs at 180 and 210 days of age and analyzed their meat quality, chemical composition, and flavor compounds using an electronic tongue, chromatographic techniques, and two-dimensional gas chromatography-time-of-flight-mass-spectrometry (GC×GC-TOF-MS). A total of 16 main fatty acids, 18 main free amino acids, and 249 flavor compounds were identified. The results showed that TB pigs exhibited redder meat color, higher intramuscular fat, and lower shear force than Duroc pigs (p < 0.05). TB pigs displayed higher levels of flavor nucleotides, free amino acids, and monounsaturated fatty acids (p < 0.05). Furthermore, pigs at 180 days exhibited lower dripping loss and more flavor compounds than those at 210 days (p < 0.05). Electronic tongue analysis revealed higher umami values in TB pigs at 180 days of age. Among the flavor compounds in pork, the four compounds that contributed most significantly to flavor across all species were 2-nonenal, 2-octenal, heptanal, 2,3-butanedione, and 2-pentylfuran. These findings provide fundamental data and insight into pig production.